Strategi Pembinaan Karakter Santri melalui Kegiatan Pengabdian kepada Masyarakat di Pesantren: Character Development Strategy for Students through Community Service Activities in Pesantren - Ipah Siti Chuzaipah (AJMIE: Alhikam Journal of Multidisciplinary Islamic Education, 2026)
This study aims to analyze the strategy of character building through community-based service activities at Pondok Pesantren Al Fadlliyah Tuban Purwaraharja Bojonggambir Tasikmalaya, particularly for sixth-grade students or third-grade Madrasah Aliyah (MA) students. The research method used is descriptive qualitative, with data collection techniques including observation, interviews, and documentation studies. Data analysis was conducted through data condensation, data display, and conclusion drawing. The results show that: (1) the planning of community service activities is carried out systematically through setting character-building objectives, selecting locations, and providing student preparation; (2) the implementation involves students actively participating in various religious and social activities, such as teaching, leading prayers, and engaging in community service; (3) the character-building process is conducted continuously through guidance, monitoring, and evaluation; and (4) community service activities have a positive impact on students’ character development, particularly in terms of independence, responsibility, social awareness, communication skills, and self-confidence. Therefore, community-based service activities can be considered an effective strategy for character building in Islamic boarding schools.